Cyber Security Assessment: A Case Study of Smart Metering Infrastructure - Khan, Zeeshan (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The Smart Metering Infrastructure (SMI) is a paradigm shift from the traditional meters providing real time connectivity between consumer to grid, which poses a critical challenge to ensure cybersecurity. The complexity and heterogeneity of SMI creates an uphill task to design a uniform solution to address various cyberattacks. The security of SMI should be viewed holistically keeping in purview the network, physical meter, database, application etc. Although, most of the international standards and guidelines are adhered to but during actual implementation, deviations are common wherein the local guidelines take preference i.e Central Electricity Authority (CEA) in the case of India. Due to many reasons such as supply chain risks or unavailability of resources, the SMI may not be equipped with the best protection measures, which may result in national crisis when seen at a larger scale. The study aims to provide an assessment of the cybersecurity posture of SMI along with measures/recommendation to make it cyber resilient.